The process of achieving the principles of the triangle area of middle school students through YouTube assisted learning during a pandemic - Rahmat Jumri; Wahyu Widada; Dewi Herawaty (International Journal of Trends in Mathematics Education Research, 2022)
The purpose of this study was to describe the achievement of the triangular principle of junior high school students through YouTube-assisted learning during the COVID-19 pandemic. It is exploratory research. The subjects of this study were middle school students in Bengkulu City, Indonesia. We conducted task-based interviews with twenty-one people. The data from the completion of the task was analyzed early to determine their level of thinking. It was using its genetic decomposition. We classified them into five levels of schema development. We selected students who were at the trance level for further in-depth interviews. We use audio-visual recorders to get complete and accurate data. Data were analyzed by applying qualitative data analysis techniques. The results of this study were 19% of the research subjects were at the intra level, 33% were at the semi-inter level, 33% were at the inter level, and 10% of the subjects were at the inter level, and only one person who was at the trance level (= 5%). The conclusion of this study is that students who are at the highest level are able to build relationships between actions, processes, objects, and previous schemas so that a mature schema is formed about the area of the triangle.